EFEKTIVITAS IMPLEMENTASI PENANGANAN LAPORAN MALADMINISTRASI DI OMBUDSMAN RI PERWAKILAN JAWA TIMUR - Firdaus, Muhammad Rizqy; Aminullah, Aminullah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Maladministration in public service delivery remains a critical issue in establishing a responsive and accountable bureaucracy. The Indonesian Ombudsman serves as an oversight institution tasked with addressing public complaints related to suspected administrative misconduct. This study adopts a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The research was conducted at the East Java Regional Office of the Indonesian Ombudsman. Field findings indicate that the effectiveness of maladministration complaint handling still encounters several challenges, including limited resources, low public participation, and suboptimal coordination among related institutions. The study applies the implementation framework proposed by Sanford and Moulton, which emphasizes three key indicators: the context of change, core program design, and technical-adaptive challenges. The analysis reveals that although the implementation of complaint handling has shown progress, its overall effectiveness has yet to reach its full potential. This research aims to analyze the effectiveness of maladministration complaint handling and to identify the barriers encountered during its implementation at the East Java Office of the Indonesian Ombudsman.